2015
DOI: 10.5539/jas.v7n4p144
|View full text |Cite
|
Sign up to set email alerts
|

Immediate and Transgenerational Regulation of Plant Stress Response through DNA Methylation

Abstract: Epigenetics refers to the heritable changes in gene activity without altering the DNA sequence. DNA methylation along with other epigenetic mechanisms is involved in the chromatin remodeling. This remodeling, especially in plants, plays an important role in the activation or silencing of specific genes as well as other genomic regions in response to the developmental and environmental clues. Environmental clues, biotic and abiotic stresses trigger the shift in the site specific as well as genome wide DNA methy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Such changes include paramutations, transgene silencing, genome imprinting and transposon inactivation that are widespread in plants [106]. These changes are highly dynamic and transitory throughout the development of an organism and are mitotically and/or meiotically transmissible [107][108][109][110][111]. Histone modifications such as methylation, acetylation and sumoylation, and remodeling of the chromatin structure [112] result in either gene activation or silencing ultimately affecting processes such as plant development [109,113].…”
Section: Plant Epigenetics and Endosperm Developmentmentioning
confidence: 99%
See 2 more Smart Citations
“…Such changes include paramutations, transgene silencing, genome imprinting and transposon inactivation that are widespread in plants [106]. These changes are highly dynamic and transitory throughout the development of an organism and are mitotically and/or meiotically transmissible [107][108][109][110][111]. Histone modifications such as methylation, acetylation and sumoylation, and remodeling of the chromatin structure [112] result in either gene activation or silencing ultimately affecting processes such as plant development [109,113].…”
Section: Plant Epigenetics and Endosperm Developmentmentioning
confidence: 99%
“…Methylated cytosines are seen in major eukaryote groups such as plants, fungi and animals [110]. In plants, DNA methylation occurs at CG, CHG and CHH sites [106,115,116].…”
Section: Plant Epigenetics and Endosperm Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…There are extensive studies showing the relationships between DNA methylation and abiotic stresses [ 21 ]. It was shown that the decrease in the salt tolerance capability of Arabidopsis coincided with the blocking of DNA methylation at cytosine by 5-azacytidine treatment [ 22 ].…”
Section: Mechanisms Of Srna-mediated Genetic Regulationmentioning
confidence: 99%